Ill. Act of Apr. 16, 1881 - (:unkn) unknown (General Publisher, 1881)
Prohibited the concealed carry or brandishing of any slung-shot, metallic knuckles, pistol, revolver, derringer, bowie knife, dirk, or other deadly weapon of like character. Violators punished by fine not less than twenty-five dollars nor more than two hundred dollars.
--
Keywords: CARRY - CONCEALED